HUBUNGAN DEFISIENSI KADAR ZINC TERHADAP MEMORI PADA ANAK USIA SEKOLAH - , SETIANINGSIH, Prof.dr.Djaswadi D, SpOG(K), MPH, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: More than two billion people are expected to lack essential vitamins and minerals, especially vitamin A, iodine, iron (Fe) and zinc (Zn). Research showed the positive effect of zinc supplementation on children's growth, morbidity and mortality in diarrhea and pneumonia. Zinc plays an important role in the structure and function of the brain, so that zinc deficiency can also harm behavior in the development of cognitive functions, namely attention and memory. Objective: To determine the effect of zinc deficiency on memory in school-age children in the district of Klaten. Method: The study used was description of analytic with quantitative approach using cross-sectional design. The experiment was conducted in some primary schools (SD) in the district of Klaten. The study population was all primary school children aged 9-12 years which the sample accordance with inclusion and exclusion criteria. The sampling technique was done by purposive sampling to represent SD of villages and towns. The determination of the samples by PASS software and the number of sample was 60. Data analysis used univariable, bivariable and multivariable by statistical test t-test and linear regression with 95% confidence intervals. Results: The analysis showed that children with zinc deficiency has the average value of 6.1 short -term memory with SD 1.3, whereas children with normal zinc levels had the average value of 10.7 and SD 3.1. The mean difference of -4.6 with 95 % CI (-6.98 - (-2.14) and a value of p = 0.0004 or p < 0.05. Children with zinc deficiency the average value of long-term memory were 7.8 with SD 3.0, whereas children with normal zinc levels the average value was 8.4 and SD 3.2. The difference of the mean was -0.57 with 95 % CI (-3.16 - 2.01) and a value of p = 0.658 or p > 0,05. Conclusion: The average scores value of short-term memory in children with zinc deficiency was lower than the short-term memory scores in children with normal zinc levels. The average scores value of long-term memory in children with zinc deficiency equal to the children with normal zinc levels.